FIRST PRINCIPLES CALCULATIONS FOR STRUCTURAL AND MECHANICAL PROPERTIES OF POLAR INTERMETALLICS TYPE LAVES PHASES YM2 (M: NI, CU AND ZN) (Journal of Sciences & Technology, 2016)
Polar intermetallics type Laves phases play in recent years a very important role in the field of metallurgy, and subject to a large number of works related among other things to their crystal chemistry and stability of their structures. In this paper we used a simulation study and ab initio based on the DFT, to examine the structural stability and to appreciate the mechanical properties of these compounds YM2 (M: Cu, Zn, Ni).